Incidence of Tuberculosis During the First Year of Antiretroviral Treatment in West African HIV-Infected Adults. (2nd June 2020) - Tchakounte Youngui, Boris; Coffie, Patrick; Messou, Eugène; Poda, Armel; Fortes Deguenonvo, Louise; Hawerlander, Denise; Minga, Albert; Balestre, Eric; Dabis, François; Marcy, Olivier
Abstract: We estimated tuberculosis incidence during the first year on antriretroviral therapy without isoniazid-preventive treatment in 6938 West African HIV-infected adults at 3.33 cases per 100 person-years (95% CI, 2.85–3.80). In multivariate Poisson models, sites in Cote d'Ivoire, male gender, low body mass index, low hemoglobin, low CD4 count, and young age were significantly associated with higher incidence.